Early microlesion of viral encephalitis confirmed by galectin-3 expression after a virus inoculation. (10th April 2015) - Kobayashi, Kazuhiro; Niwa, Masayuki; Hoshi, Masato; Saito, Kuniaki; Hisamatsu, Kenji; Hatano, Yuichiro; Tomita, Hiroyuki; Miyazaki, Tatsuhiko; Hara, Akira
Highlights: We examine galectin-3 expression in CNS after EMCV inoculation. Galectin-3 is up-regulated in several degenerated lesions 96 h after EMCV. Iba-1 positive microglia was activated within and around the focus of infection. Microlesions with a few galectin-3 positive cells were detected in cerebellum at 48 h. Galectin-3 is a key mediator between viral infection and neuronal degeneration. Abstract: Galectin-3 is a β-galactosidase-binding lectin which is important in cell proliferation and apoptotic regulation. Encephalomyocarditis virus (EMCV), which includes the Enterovirus genus, can cause not only acute myocarditis but also neuronal degeneration of central nervous system in various animals including mice. The pathophysiological role of galectin-3 in central nervous system following acute viral infection is not fully understood. The goal of this study is to determine the localization and time-course of galectin-3 expression after acute viral inoculation with EMCV. Galectin-3 is up-regulated in degenerated lesions of brain area including cerebellum, hippocampus, thalamus and cerebral hemisphere, 96 h after EMCV inoculation. At the same time, Iba-1 positive microglia was morphologically activated within and around the focus of infection. Interestingly, in cerebellum, the microlesions containing a few galectin-3 cells were detected in the immediate-early phase of infection, as early as 48 h after EMCV inoculation. Thus, our results indicate that galectin-3 expression may be a key mediator between viral infection and neuronal degeneration in central nervous system including cerebellum. Furthermore, detection of galectin-3 might be an early diagnostic method for neuronal degeneration after virus infection.